How augmented reality, textual, and collaborative scaffolds work synergistically to improve learning in a science museum. Issue 3 (3rd July 2018) - Yoon, Susan A.; Anderson, Emma; Park, Miyoung; Elinich, Karen; Lin, Joyce
Abstract: Background: This study builds on a series of studies that examined how augmented reality and various other learning scaffolds can promote deeper conceptual and cognitive understanding among visitors in a science museum. Purpose: We focus specifically on determining the exact affordances of different genres of scaffolds that include augmented reality, text-based, and collaborative scaffolds and how they work synergistically to support learning. Sample: This study took place in a science museum in a large northeastern city in the United States. We worked with 374 youth, 47% female and 53% male, in grades 5 through 8 who visited the museum as part of a school field trip. The students attended public schools in the city and greater metropolitan region. Design and methods: Students interacted with one of two devices, Magnetic Maps or Bernoulli Blower. Groups of two or three were randomly selected to interact with the device in one of four conditions that had varying numbers of scaffolds. We collected and analyzed data from student worksheets, interviews, and observation videos. All data sources were qualitatively analyzed for scaffolding affordances based on known qualities derived from the literature. Results: The greatest affordance of the AR scaffold was the ability to access hidden information. The most helpful aspect of the text-based scaffolds was the ability to provide instructions on how to interact with the exhibit. The most useful aspect of the collaborative scaffolds was the ability to receive feedback on one's own understanding. Video observations showed that student learning increased when all three scaffolds were synergistically accessed. Conclusions: This study has implications for how to design for learning in a museum. Many exhibits have distributed scaffolds where different devices aid in the learning of the overall phenomena. However, results from this study suggest that more learning can take place when visitors have access to multiple scaffolds at the same time.